Molecular Identification and Characterization of Lipase-Producing Bacteria Isolated from Wawolesea Hot Spring, Southeast Sulawesi - Sapto Raharjo; Muhammad Azwar Syah; Andi Tantri; Tien Tien; Lina Lestari (Biology, Medicine, & Natural Product Chemistry, 2026)
The Wawolesea hot spring in Southeast Sulawesi represents an extreme ecosystem characterized by high temperature and salinity, providing a potential habitat for thermo-halophilic bacteria that produce industrial enzymes, particularly lipase. Here, we carried out molecular identification of lipase-producing bacteria isolated from the Wawolesea hot spring using 16S rRNA gene analysis. The sequence comparison showed that isolate K.111 was the most closely related to Bacillus thuringiensis. This supports the hypothesis that the Wawolesea hot spring harbors thermo-halophilic bacterial communities with potential applications in industrial biocatalysis.